Get out the vote – or else: the impact of fear of election violence on voters. Issue 4 (18th May 2020) - Burchard, Stephanie M.
ABSTRACT: Previous research has found little systematic evidence that election violence has any uniform effect on voter turnout. Nonetheless, its continued strategic use, especially by incumbent governments, suggests that many politicians believe violence somehow helps win elections. Using survey data from 32 African countries, I examine the impact of fear of election violence on vote intention and candidate support at the presidential level. Similar to findings from the literature on negative campaigning, fear of election violence appears to mobilize support, but only for opposition candidates. Fear of election violence is associated with increased support for opposition candidates by both opposition party members and non-partisans. Furthermore, it appears to produce a backlash effect for incumbent candidates, decreasing their support among non-partisans. Fear of election violence, rather than increasing the chance of victory, could be costing incumbents support at the polls.